(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Intra abdominal infection is a common acute disease with a high mortality rate in the surgical intensive care unit of Viet Duc University Hospital. Determining the cause of the disease and the level of antibiotic resistance of bacteria is very important in orienting early treatment with empirical antibiotics. Subjects and methods: Cross-sectional descriptive study on patients with abdominal infections treated at Intensive Care Department 1 and 2, Viet Duc University Hospital from January to June 2024. Specimens were taken during surgery or under ultrasound to send microorganisms to culture and identify bacteria. Results: There were 47 patients with intra abdominal infection in the study. Patients admitted to the intensive care unit are often in a state of septic shock with a SOFA score in 24 hours upon admission of 8 ± 3.9, pathological causes accounted for 70%, trauma 30%, average treatment time was 17 days. The mortality rate is up to 34%. From patient samples, 52 bacterial strains were isolated, Gram-negative bacilli accounting for 65.4%. The three most common bacterial strains in intra abdominal infections are Enterococcus 28.8%, Escherichia coli (23%), Klebsiella (25%). The rate of bacteria resistant to Ampicillin was 87%, Ciprofloxacin 79.4%. Enterococcus was 78.5% resistant to tygecycline, 1 sample was resistant to vancomycin. The bacteria group Klebsiella, Acinetobacter, and Pseudomonas had the strongest antibiotic resistance, 93.3% were resistant to meropenem, 92.5% with Ciprofloxacin and Levofloxacin. Conclusions: Patients with intra abdominal infections admitted to the intensive care unit are often in a state of severe septic shock, require long-term treatment, and have a high mortality rate. Gram-negative bacteria are the common cause of 65.4% of diseases, with a high level of antibiotic resistance.